Characterization of the Growth of Herpes Simplex Virus in Human Lymphoid Cells - Mizrahi, A. (1972)
Herpes simplex virus was grown in a 6-liter suspended culture of an atypical permanent human lymphoid cell line, Roswell Park Memorial Institute no. 8226. The kinetics of virus replication were determined by counting viruses by electron microscopy, plaque formation, and tissue culture infectivity. Deoxyribonucleic acid-dependent deoxyribonucleic acid polymerase activity was determined during the course of infection. Electron microscopy studies substantiated the kinetics of the virus infection in lymphoid cells.